Stability of surrounding rock with water accumulation in goaf - JIN Changyu; WEI Zhenlin; CHEN Tianyu (矿业科学学报)
This study investigates the influence of water accumulation in goaf on the stability of surrounding rock in a coal mine in Shanxi Province via field test, laboratory experiment and numerical simulation. Specifically, we established 3D geometric models of water bodies and goaf in water-bearing goaf based on 3D laser scanning and sonar. We then conducted permeability test on coal rock under different degrees of damage, and obtained permeability variation patterns. We then analyzed the stability of surrounding rock near water-cut goaf using numerical software by considering the dynamic changes of permeability. Results show that: ① pore water pressure exerts significant impact on the surrounding rock and overlying rock mass. ② The surrounding rock is prone to water seepage and percolation after the old goaf is flooded. ③ A large range of plastic zone with low stability is observed in the coal pillar between the goaf and roadway due to mining disturbance and water seepage. Therefore to ensure the safety of underground production, it is suggested to increase temporary underground drainage facilities for in-time water discharge to avoid flooding accidents.